1993
DOI: 10.1007/bf00593974
|View full text |Cite
|
Sign up to set email alerts
|

Unilocular orbital, cerebral and intraventricular hydatid cysts: CT diagnosis

Abstract: A 10-year-old girl with surgically proven unilocular hydatid cysts within the frontal horn of the right lateral ventricle, in the right orbit and another the left frontal region is reported. The intraventricular cyst was diagnosed on CT examination with intrathecal contrast medium injected via lumbar puncture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0
3

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 12 publications
4
37
0
3
Order By: Relevance
“…Analysis of records showed that out of 9 pediatric cases, only 4 cases had unruptured evacuation, giving a 44% rate of hydatid birth. Comparing this rate in the pre-CT era with a 70% intact removal rate (14 patients) in 20 pediatric cases operated on within the next 20 years – mostly in the CT era – reveals the invaluable place of high-technology diagnosis in neurosurgery [49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65]. Only 1 case out of 14 with CT had a misdiagnosed preoperative lesion (extradural retroclival hydatid cyst), as published in 1994 by Canbolat et al [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of records showed that out of 9 pediatric cases, only 4 cases had unruptured evacuation, giving a 44% rate of hydatid birth. Comparing this rate in the pre-CT era with a 70% intact removal rate (14 patients) in 20 pediatric cases operated on within the next 20 years – mostly in the CT era – reveals the invaluable place of high-technology diagnosis in neurosurgery [49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65]. Only 1 case out of 14 with CT had a misdiagnosed preoperative lesion (extradural retroclival hydatid cyst), as published in 1994 by Canbolat et al [33].…”
Section: Discussionmentioning
confidence: 99%
“…Besides the classical CT appearance, which shows a cystic lesion spherical in shape with a sharply defined border and absorption value similar to that of cerebrospinal fluid [33, 34, 50, 59, 63], and characteristic magnetic resonance image [58, 61, 62, 64]revealing a cyst with a low-intensity rim, by the advance of new technologies, the characteristic features of in vivo proton magnetic resonance spectroscopy in intracranial hydatid cysts are described [65]. A large resonance for pyruvate was observed, besides lactate, alanine and acetate, and Kohli et al [65]concluded that in vivo magnetic resonance spectroscopy may be used as an adjunct to imgaing in the diagnosis of intracranial hydatid cysts and may also have a role in monitoring the drug therapy, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Deve (1921) and Demaria (1919) successfully demonstrated the development of a hydatid cyst experimentally in the eyes of experimental animals. Orbital hydatid cysts are usually located on the supero-lateral or supero-medial aspect of the orbit [10].…”
Section: Discussionmentioning
confidence: 99%
“…12, 13). There is usually neither calcification (1 %) nor perifocal edema, although there is considerable mass effect and there may be hydrocephalus [13][14][15][16][17].…”
Section: Brainmentioning
confidence: 98%